Influence of pulse duration on surface roughness in assisting electrode electric discharge machining - Rodić, Dragan; Marin, Gostimrović; Milenko, Sekulić; Madić, Miloš; Nenad, Kulundžić (Journal of Production Engineering, 2022)
Electrical discharge machining (EDM) is an unconventional machining process that can machine all electrically conductive materials, regardless of their physical and metallurgical properties. Due to the efficiency of machining modern engineering materials, existing EDM methods are constantly being researched and improved or developed. This paper deals with an innovative method that enables EDM machining of non-conductive ceramic material, named Assisting Electrode Electrical Discharge Machining (AEEDM). It combines electrical discharge machining with a hybrid assisting electrode. The aim of the study is to find the influence of pulse duration on surface roughness. For the set machining conditions, it was found that the surface roughness was increased by increasing the pulse duration. It should be emphasized that the supporting electrode method is used only in the electroerosion of electrically non-conductive materials.